(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The Republic of Armenia (RA) is a typical mountainous country. Horizontal and vertical fragmentation of the area, severe climate conditions and other naturalgeographical phenomena narrow the inhabitation areal of RA. This factors directly and indirectly affect the development of rural areas. In the article, based on the analysis and generalization of factual and statistical data, the role of rural areas and settlement pattern in the development of mountainous and high mountainous areas is substantiated on the example of RA.